Effects of inclusion Aspergillus niger fermented shrimp waste meal in broiler diets on live performance and digestive organ weight - Djunaidi, Irfan H.; Yuwanta, Tri; ., Supadmo; Nurcahyanto, M. (Indonesian Journal of Animal and Veterinary Sciences, 2009)
An experiment was conducted to evaluate the effect of the inclusion of different levels of shrimp waste meal fermented with Aspergillus niger (LUF) in diets on growth performance and digestive organ weight of broilers. A total of 75 d-old chicks were randomly allocated to 5 (five) treatments in 3 replication pens of 5 birds each. Treatments consisted of LUF inclusion of 0 (control), and 5, 7.5, 10 and 12,5% (P0, P1, P2, P3 and P4) in the diets. Birds were raised under standard condition and provided with feed and water ad-libitum. Feed and birds were weighed weekly up to 35 days to determine body weight, feed intake and feed conversion. At the end of experimental period, the birds were slaughatered and dressed up to determine carcass percentage and digestive organ weight. There was a significant negative linear response in body weight, feed consumption and feed conversion with increase of LUF more than 7.5% in the diets until 35 days of age, but % carcass was almost the same for all treatment. There was no significant response in digestive organ weight with increasing levels of LUF. The present result indicated that LUF could be considered as a potential feed ingredient as protein source of broiler but its inclusion should be limited until 7.5% of the diet to maintain growth performance and digestive organ weight. Key words: Shrimp Waste Meal, Broiler, Growth Performance, Digestive Organ Weight